2018
DOI: 10.1186/s12974-018-1193-6
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid attenuates traumatic spinal cord injury-induced inflammation via STAT1 and NF-κB pathway dependent of HDAC3

Abstract: BackgroundMicroglial polarization with M1/M2 phenotype shifts and the subsequent neuroinflammatory responses are vital contributing factors for spinal cord injury (SCI)-induced secondary injury. Nuclear factor-κB (NF-κB) is considered the central transcription factor of inflammatory mediators, which plays a crucial role in microglial activation. Lysine acetylation of STAT1 seems necessary for NF-kB pathway activity, as it is regulated by histone deacetylases (HDACs). There have been no studies that have explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
169
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(180 citation statements)
references
References 42 publications
10
169
1
Order By: Relevance
“…Diverse neurotrophic factors have contributed to the poor axonal regrowth and ineffective functional recovery in the SCI repair process (Chen et al, 2018a,2018b; Mesentier‐Louro et al, 2019). It has been reported that glial cell line‐derived neurotrophic factor (GDNF) has protective potential in neurodegeneration disease(Mukhamedshina et al, 2016).…”
Section: Sustained Release Of Neurotrophic Factors By Chitosan Complementioning
confidence: 99%
See 1 more Smart Citation
“…Diverse neurotrophic factors have contributed to the poor axonal regrowth and ineffective functional recovery in the SCI repair process (Chen et al, 2018a,2018b; Mesentier‐Louro et al, 2019). It has been reported that glial cell line‐derived neurotrophic factor (GDNF) has protective potential in neurodegeneration disease(Mukhamedshina et al, 2016).…”
Section: Sustained Release Of Neurotrophic Factors By Chitosan Complementioning
confidence: 99%
“…However, the existing treatment strategies have not exhibited significant potential to cure SCI. The pathophysiologic mechanism of SCI is complicated and includes the loss of neurons and glial cells, degeneration of extracellular matrix architecture and destruction of the neural circuit at the lesion site (Kumar et al, 2015; Chen et al, 2018a). Current strategies to cure SCI include surgical decompression (Jug et al, 2015; Liu et al, 2016) and pharmacotherapy (Wang et al, 2019) as well as focus on the restoration of nerve function by enhancing the survival of neurons after injury and promotion of axon regeneration via the injury site.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that systemic administration of valproic acid (VPA) improved locomotor function after SCI (6)(7)(8). In addition, VPA exerts an anti-inflammatory effect (9), reduces cell death of motor neurons (10) and cellular apoptosis (11), attenuates demyelination and axonal loss, preserves the oligodendrocytes and neurons (6), increases neurite outgrowth (12), reduces the cystic cavity (8), and increases expression of neuronal progenitor cells in the spinal cord (13).…”
Section: Introductionmentioning
confidence: 99%
“…12 This molecule has also shown intrinsic antiviral activity probably due to its activity as histone deacetylase inhibitor. 9,[13][14][15][16] VPA has shown anti-inflammatory activity in myocardial 17 as well as neural tissue in models of brain and spinal cord injuries, 18,19 although with some conflicting findings. 20 Although long-term adverse effects and even pro-inflammatory consequences have been reported with the chronic use of VPA, 12 we believe that, given the urgent need to have .…”
Section: Introductionmentioning
confidence: 99%